Efektivitas Kinerja Keuangan Pemerintah Provinsi Sumatera Utara Dalam Rangka Meningkatkan Pendapatan Asli Daerah Guna Mendorong Pertumbuhan Ekonomi - Tania Damme Sihombing; Latersia Br. Gurusinga; Yusnaini Yusnaini (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyze the effectiveness of the financial performance of the Government of North Sumatra Province in increasing Regional Original Revenue (PAD) to stimulate regional economic growth. The study is grounded in the importance of effective and efficient regional financial management as a means to strengthen regional financial capacity and ensure equitable economic development across all areas. The research employs a descriptive qualitative approach, using data collection techniques such as literature review, observation, and document analysis, including Budget Realization Reports (LRA), Regional Government Financial Reports (LKPD), and Gross Regional Domestic Product (GRDP) data from 33 regencies/cities in North Sumatra Province during the 2021–2023 period. The findings reveal that although there is a growing trend in PAD realization and the financial management effectiveness in several regencies/cities is categorized as fairly to highly effective, the contribution of PAD to economic growth remains uneven. Dependence on specific types of revenue and the low proportion of productive capital expenditures are the main obstacles to optimizing the use of PAD. This study concludes that improving the effectiveness of regional financial performance requires diversification of PAD sources, strengthening of financial management systems, and allocating budgets to strategic and productive sectors that directly support inclusive and sustainable economic growth in North Sumatra Province.